Evaluasi Atas Implementasi Pasal 45A UU Mahkamah Agung - Asril, Asril; Prasidi, Dimas (Jurnal Hukum dan Peradilan, 2012)
The high of arrears cases at the Supreme Court in the early 2000s pushed through the Blueprint for Reform Supreme Court in 2003 to require the regulation limiting the appeal court in law. The request was eventually fulfilled in part by the Parliament and the Government. In 2004 the Parliament and the Government to revise Law. 14 of 1985 on the Supreme Court through Law no. 5 of 2004. In law there is a set of 3 (three) types of cases that can not be appealed, the pretrial, the threat of criminal criminal highest 1 year in prison and a case in which the decision of the State Administrative TUN officials disputed that its range is only in the area. But after the law was passed that the case turns into flows MA instead of decreasing but increasing. Many factors are causing the higher the current case, but an evaluation of the effectiveness of regulations limiting case still deemed necessary. This study is intended for this purpose. In this simple study researchers tried to test some of the provisions limiting case, that restrictions on criminal cases the threat of criminal highest 1 year in prison and / or fines. Keywords: Evaluation, Implementation, Supreme Court